Alōkanaṃ - Hanumacchāstri, Jānamaddi (Mitra Samūha, 2018)
Autobiographical reminiscences of a Telugu literary critic, scholar, teacher, and social activist from Andhra Pradesh, India
Keywords: Autobiografie; Hanumacchāstri; Jānamaddi; Critics; Authors; Telugu; Teachers; Social workers; Biographies